Evaluation of forest conversion effects on soil erosion and soil organic carbon using 137Cs and 210Pbex tracers in the low mountain–hill region of Southwest China - Chu, Junzhi; Cao, Yang; Shen, Yuyi; Teng, Qiumei; Liao, Jialin; Sun, Yingjie; Zhang, Denan; Liang, Yueming; Huang, Kechao; Shi, Hao; Xu, Guangping (Frontiers in Environmental Science, 2026)
Estimating both soil erosion and sedimentation in southern China’s hilly regions is essential for planning soil-conservation measures; however, the patterns of soil erosion and their influence on soil organic carbon (SOC) in different forest types remain insufficiently understood. Using a dual-tracer approach with 137Cs and 210Pbex, this study assessed soil erosion dynamics across three forest types --mixed broadleaf forest (MBF), Masson pine plantation (MPP), and Eucalyptus plantation (EUP) --in the low mountainous hills of northern Guangxi, southwest China. Both radionuclides showed exponential declines in activity concentrations with depth, with pronounced surface enrichment (peak values in the 0–5 cm layer) in all forest types. EUP exhibited significantly lower clay content and higher sand proportions compared with MPP and MBF, and SOC content was consistently lowest in EUP across all slope gradients. Mean 137Cs and 210Pbex inventories followed the order MBF > MPP > EUP, while slope position followed lower-slope > mid-slope > upper-slope. Soil erosion rates ranged from -466.90 to 2159.78 tkm-2a‐1 for 137Cs and 210Pbex and -398.83 to 3023.27 tkm-2a-1 for 210Pbex, with erosion intensity increasing from lower to upper slopes and being highest in the Eucalyptus plantation. Significant positive correlations (p<0.01) were observed between both radionuclides and SOC and clay content. Overall, the conversion of mixed forests to economic plantations intensified soil erosion, particularly in EUP. Targeted management practices in EUP are essential for improving soil conservation and promoting sustainable forest management. The close agreement between 137Cs and 210Pbex‐derived erosion estimates highlights the potential of 210Pbex as an alternative or complementary tracer for monitoring soil erosion in this region.